2020
DOI: 10.1103/physreva.102.050801
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmically enhanced Euler-Heisenberg Lagrangian contribution to the electron gyromagnetic factor

Abstract: Contrary to what was previously believed, two-loop radiative corrections to the g-factor of an electron bound in a hydrogen-like ion at O α 2 (Zα) 5 exhibit logarithmic enhancement. This previously unknown contribution is due to a long-distance light-by-light scattering amplitude. Taking an effective field theory approach, and using the Euler-Heisenberg Lagrangian, we find ∆g = − α π 2 (Zα) 5 56π 135 ln Zα.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In particular, for the 2s 1/2 and 2p 1/2 levels the oneloop thermal corrections at T = 300 K are on the level of precision anticipated in the forthcoming experiments [62]. This contribution is comparable to various previously investigated higher-order effects, such as the bound-state two-loop QED contributions [63], in particular, the two-loop virtual light-bylight scattering [28,29,64]. We note that the results for the 2s and 2p states are relevant not only for the excited states of Hlike ions, but also for the ground states of Li-and B-like ions, respectively.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In particular, for the 2s 1/2 and 2p 1/2 levels the oneloop thermal corrections at T = 300 K are on the level of precision anticipated in the forthcoming experiments [62]. This contribution is comparable to various previously investigated higher-order effects, such as the bound-state two-loop QED contributions [63], in particular, the two-loop virtual light-bylight scattering [28,29,64]. We note that the results for the 2s and 2p states are relevant not only for the excited states of Hlike ions, but also for the ground states of Li-and B-like ions, respectively.…”
Section: Resultssupporting
confidence: 67%
“…To match experimental precision, a rigorous account of relativistic, QED, and nuclear (including recoil, finite size, and polarization) effects is needed [17][18][19][20][21][22][23][24][25][26][27][28][29]. Even the impact of the gravitational field of the Earth [30] or instability of external fields affecting atomic characteristics [31] are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, we can consider even more complicated QED bound-state observables, for example, the bound electron g-factor [96][97][98][99]. In this case, one has a triple expansion in powers of (Zα), α and ln(Zα), where Z is atomic charge.…”
Section: Jhep09(2021)122mentioning
confidence: 99%
“…Beside this, we included the one-loop 1/Z and 1/Z 2+ QED effects from our recent work [28] and the nuclear recoil corrections of rel-ative orders 1/Z 0 , 1/Z 1 , and 1/Z 2+ calculated by Shabaev et al [29]. Furthermore, we added the two-loop (Zα) 5 effects calculated recently by Czarnecki and co-workers [30,31] and by us [32]. The two-loop results in those studies were reported for the 1s hydrogenic state.…”
Section: Resultsmentioning
confidence: 99%